Feasibility of an unsupervised aerobic exercise training program for participants with persistent symptoms after SARS-CoV-2 infection - Carina Emmel; Oliver Bruder; Niklas Keller; Lukas Schipper; Christoph Schneider; Alexander Ferrauti; Mirjam Frank; Marcus Brinkmann; Mareike Eißmann; Thimo Wiewelhove; Börge Schmidt (Scientific Reports)
Abstract Aim of the randomized controlled pilot study was to investigate general feasibility in terms of adherence to a 12-week unsupervised aerobic exercise training program in participants with persistent symptoms (fatigue, concentration problems, breathing problems or headache) > 12 months after SARS-CoV-2 infection. Multiple symptom-related, psychosocial, spiroergometric and body composition parameters were collected at baseline and follow-up examination. The intervention group underwent a 12-week unsupervised aerobic exercise training program. The control group kept their regular physical activity. Both groups maintained an online training diary. Data was evaluated descriptively using intention-to-treat, per protocol and as-treated analysis. Feasibility of an unsupervised aerobic exercise training intervention was limited, as a large number of participants in the intervention group did not strictly adhere to the training plan. Therefore, statements about the efficacy were restricted. However, there was some weak indication for efficacy of the intervention to reduce self-rated severity of symptoms and to improve overall wellbeing. In the present study, an unsupervised aerobic exercise training intervention can be recommended only to a limited extend. The study results can be used to inform future studies designed to evaluate the efficacy of unsupervised aerobic exercise training programs in participants with persistent symptoms after SARS-CoV-2 infection.